PLANKTON FERTILITY IN SUPPORTING FISH PRODUCTIVITY IN MONOTONOUS SWAMP IN HULU SUNGAI UTARA REGENCY - Slamat, Slamat (TROPICAL WETLAND JOURNAL, 2015)
This study was carried out in a monotonous swamp in Hulu Sungai Utara Regency, South Kalimantan Province. The purpose was to find out the plankton fertility in supporting fish productivity in the monotonous swamp to build a dynamic waterbody with all of its supporting aspects. The analyses were performed on plankton diversity, water quality parameters and fish production levels from 2009 to 2013. The results of Shannon-Wiener diversity index analysis for plankton in the swamp approximately exceeded the value (>2), indicating that the water condition was still good and fertile. The water quality parameters in the swamp were specific; blackish brown in color, acid, and having low level of oxygen with high ammonia concentration. The decreasing trends of fish productivity in the swamp were resulted from unselective fish catching, environmental pollutions and land-use changes converting the swamp areas into plantations and housing. Therefore, it is necessary to develop conservation areas to keep the primary productivity of the waterbody in high level, which would affect the increase in the productivity of swamp fish.Keywords: plankton, water quality, fish productivity.